MICROBIAL TRANSGLUTAMINASE: SOURCE, PRODUCTION AND ITS ROLE TO IMPROVE SURIMI PROPERTIES - Dewi Zeswita Zilda (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Transglutaminases (EC 2.3.2.13) have attracted a wide interest from both scientific and appliedpoints of view due to their capacity to cross-link protein substrates. Obtaining transglutaminasesderived from animals are extremely high cost process, which has hampered its wider applicationuntil the discovery of transglutaminase produced by microorganisms. In the early 1990, sincemicrobial transglutaminase have been found, many transglutaminase-producing microbial strainshave been isolated and the enzyme production processes have been optimized. This resulted in the increased uses of transglutaminases in the food industries. In the fisheries industry, MTGasehas successfully been used to improve the mechanical properties of surimi from various fishes.